The new enhancement of OLSR energy-saving system in ADHOC network / Suhazlan Suhaimi - Suhaimi, Suhazlan (2018)
In Mobile Ad Hoc Networks (MANETs), network nodes typically have short lifespans given that they are mobile, self-reconfigurable, and dependent on the battery power. To help mitigate such a problem, the Optimize Link State Routing protocol (OLSR) is considered the most appropriate routing protocol to extend nodes’ lifespans. As such, this study was undertaken with the main aim to enhance the energy-saving system of MANET, with which nodes can function without failure by using a newly developed algorithm of the OLSR protocol. Specifically, the study involved the developments of three schemes, namely a new Load Balance Energy Distributed (LBED) scheme, a new enhancement energy-saving (NEES) scheme, and a New Enhanced OLSR Willingness Calculation (NEWC) scheme. Accordingly, a series of simulations was carried out to measure and quantify the performances of the LBED, NEES and NEWC schemes using the OLSR protocol. The performance criteria were based on the level of remaining battery power (measured in percentage points), energy consumption, and number of live nodes based on high data transmission rate and high mobility speed requirements. The simulations performed yielded several promising, interesting results. The new enhanced energy-saving system was able to improve the battery power consumption significantly by as much as 20%. Most promising, the mean percentage of network improvement using the new enhancement energy-saving system was 48.18%, which was significantly high compared to that of existing OSLR protocol. Such findings suggest that the new enhancement energy-saving system will be able to further improve the performance of MANETs by making such networks more stable and reliable. In addition, the new enhancement energy-saving system was applied to a number of network scenarios based on high mobility speed and high data transmission rate, the findings of which helped formulate a solution matrix. This matrix can serve as a network configuration tool to help guide practitioners (especially network administrators) in setting up appropriate mobile networks that are badly needed to establish communication in critical situations involving highly mobile nodes. Overall, the research findings suggest that the proposed new enhancement energy-saving system of the OLSR protocol can help improve the use of battery energy in MANETs through efficient distribution of energy to network nodes. Effectively, such energy-efficient distribution can help prolong the life of each node, directly improve the selection of nodes as MPR nodes, provide more alternative routes in the network, and evenly distribute data transmission tasks to all nodes. Furthermore, the findings underscore the importance of selecting appropriate levels of critical parameters (e.g., the number of nodes, size of the network space, mobility speed, and data transmission rate) that collectively will have a huge impact on the mobile network performance. In this regard, practitioners can refer to the solution matrix to select the most appropriate levels of such parameters that can help optimize the energy consumption of the battery, thus leading to a stable, reliable mobile network.